Peran Mediasi Overconfidence dan Persepsi Risiko pada Hubungan Literasi Keuangan terhadap Keputusan Investasi Generasi Z di Semarang - Krisna Kurniawan; Pradana Jati Kusuma; Dwi Eko Waluyo; Fakhmi Zakaria (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The increasing number of Generation Z investors in Indonesia indicates that investment decisions are influenced not only by financial literacy but also by psychological factors. This study aims to explore the impact of financial literacy on investment decisions, using overconfidence and perceived risk as mediating variables, and focusing on Generation Z investors in Semarang. A quantitative approach was used, with a sample of 123 respondents and PLS-SEM analysis conducted using SmartPLS 4 software. The results show that financial literacy, overconfidence, and perceived risk all have a significant positive impact on investment decisions. Furthermore, overconfidence and perceived risk mediate the relationship between financial literacy and investment decisions. These findings suggest that good financial literacy helps investors make more accurate investment decisions.